2020
DOI: 10.29333/aquademia/8443
|View full text |Cite
|
Sign up to set email alerts
|

Students Perception of Mobile Learning during COVID-19 in Bangladesh: University Student Perspective

Abstract: The aim of this study is to measures the student's perception of using mobile for learning during COVID-19 in Bangladesh especially at the university student's perspective. During the COVID-19 pandemic period, mobile learning may help the students to fulfill the study gap. Due to COVID-19 pandemic 213 countries, higher education has affected all over the world of June 2020. Although all of the developed countries considered mobile learning as an effective tool for education, it is not used properly in Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 36 publications
3
79
0
4
Order By: Relevance
“…This segment"s true picture is calculated by using the percentage. Furthermore, the mean denotes the overall average of subjects" responses, while the standard deviation indicates the variation in subjects" responses to a question (Biswas et al, 2020).…”
Section: University Students' Perception Toward Covid-19 Vaccination Programmentioning
confidence: 99%
“…This segment"s true picture is calculated by using the percentage. Furthermore, the mean denotes the overall average of subjects" responses, while the standard deviation indicates the variation in subjects" responses to a question (Biswas et al, 2020).…”
Section: University Students' Perception Toward Covid-19 Vaccination Programmentioning
confidence: 99%
“…Faculty members are willing to teach in online classes but universities do not provide faculty members with sufficient technical resources and assistance to conduct successful online classes. Biswas et al. (2020) reported that all developing countries deemed mobile learning to be an effective educational tool, but in Bangladesh, it was not used properly.…”
Section: Introductionmentioning
confidence: 99%
“…frequency of respondents answer (Biswas et al, 2020). The first dimension comprised of seven items were adapted by Kabir et al (2016a); Twum Barimah, (2015) and Wei, Hansen, ZhengLi, Liu, Sun and Bi (2014) including "Have you heard of CC before", "What are the main sources of your information on CC".…”
Section: Questionnaire Developmentmentioning
confidence: 99%